A measure of survey mode differences. (December 2016) - Homola, Jonathan; Jackson, Natalie; Gill, Jeff
Abstract: We evaluate the effects of different survey modes on respondents' patterns of answers using an entropy measure of variability. While measures of centrality show little differences between face-to-face and Internet surveys, we find strong patterns of distributional differences between these modes where Internet responses tend towards more diffuse positions due to lack of personal contact during the process and the social forces provided by that format. We introduce an entropy measure of dispersion for survey responses and illustrate its utility with election data from 2012. Our results provide clear evidence that mode matters in modern survey research, and we make recommendations for interpreting results from different modes.